Plant Engineering 2017
DOI: 10.5772/intechopen.69795
|View full text |Cite
|
Sign up to set email alerts
|

Signs of Silence: Small RNAs and Antifungal Responses in Arabidopsis thaliana and Zea mays

Abstract: Plant small RNAs (sRNAs) are pivotal regulators of gene expression, which are crucial in maintaining genome integrity and flexibility during development, abiotic and biotic stress responses. Current evidence suggests that sRNAs might be inherent to the sophisticated plant innate immune system battling bacteria. However, the role of sRNAs during antifungal plant defences is less clear. Therefore, this chapter investigates the sRNA-mediated plant antifungal responses against the hemibiotrophic fungi Colletotrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Learning from nature, plant biologists have observed that the interaction of plants with necrotising pathogens, beneficial microbes or agrochemicals can cause a sensitisation of the plant immune system, resulting in a faster and stronger induction of resistance mechanisms upon subsequent infections [ 18 , 19 , 20 , 21 ]. Memory of a past event may determine the response to future environmental stimuli, thus resulting in phenotypic and stimulus-dependent plasticity of response traits [ 22 ].…”
Section: Introduction: Multi-layered Molecular and Cellular Networmentioning
confidence: 99%
“…Learning from nature, plant biologists have observed that the interaction of plants with necrotising pathogens, beneficial microbes or agrochemicals can cause a sensitisation of the plant immune system, resulting in a faster and stronger induction of resistance mechanisms upon subsequent infections [ 18 , 19 , 20 , 21 ]. Memory of a past event may determine the response to future environmental stimuli, thus resulting in phenotypic and stimulus-dependent plasticity of response traits [ 22 ].…”
Section: Introduction: Multi-layered Molecular and Cellular Networmentioning
confidence: 99%
“…In silico differential expression analysis during interaction with P. musae, although not significant, nevertheless, indicated evidence for modulation, with increased expression in relation to controls at 12DAI, as well as down-regulation of members at both time points. Such down-regulation has also been described in the defence response to the hemibiotroph Colletotrichum graminicola in Zea mays [ 81 ].…”
Section: Discussionmentioning
confidence: 86%
“…The miRNA169 family contains four loci in Arabidopsis , with target host genes involved in a number of different processes related to plant defence and development [ 96 ]. Also responsive to PAMPs such as flg22 [ 60 ], down-regulation in Z. mays during interaction with C. graminicola has also been described, associated with increased JA signalling [ 81 ]. Here, a total of six members were expressed across the treatments, with non-significant in silico data revealing positive expression modulation during interaction with P. musae at 3DAI.…”
Section: Discussionmentioning
confidence: 99%